Polaprezinc orally disintegrating tablet and preparation method thereof
The preparation of polyprene zinc orally disintegrating tablets by co-grinding and direct powder compression method solves the problems of unstable hardness and difficulty in masking bitterness, and achieves rapid disintegration, good dissolution and stability, thereby improving the patient's compliance.
Patent Information
- Application Number
- CN202411065552.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2026-02-06
AI Technical Summary
Existing polypredicted zinc orally disintegrating tablets suffer from unstable hardness and hygroscopicity issues during the preparation process, and the bitter taste is difficult to mask, affecting patient compliance and stability.
Orally disintegrating tablets are prepared by co-grinding a combination of zinc polymethyl methacrylate (PMMA), surfactants, fillers, disintegrants and lubricants. Particle size is controlled and tablets are compressed using a direct powder compression method, which avoids the complexity of humidity control and the masking of bitterness.
The prepared orally disintegrating tablets have good hardness, rapid disintegration and dissolution properties, which improves the taste, stability and compliance, and avoids breakage and hygroscopicity problems.
Smart Images

Figure BDA0004979255040000041 
Figure BDA0004979255040000042 
Figure BDA0004979255040000051
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of pharmaceutical preparations, and particularly relates to a polaprezinc orally disintegrating tablet and a preparation method thereof. BACKGROUND
[0002] Polaprezinc, also known as L-carnosine zinc, carnosine zinc, (S)-2-(3-aminopropanoylamino)-3-(1H-imidazol-5-yl)propanoic acid zinc complex, contains 23% zinc and 77% L-carnosine, wherein zinc can promote wound healing, and L-carnosine is a dipeptide antioxidant composed of beta-phenylalanine and L-histidine. Studies have shown that polaprezinc can provide mucosal protection by increasing the expression of heat shock proteins and exhibiting antioxidant and anti-apoptotic effects, thereby improving the defense of gastric mucosa; at the same time, it can also inhibit the expression of inflammatory factors and stimulate the proliferation and migration of granulation tissue of damaged epithelial cells, thereby achieving the effect of preventing and treating peptic ulcer. It has obvious inhibitory effect on models of peptic ulcer such as gastric mucosal damage caused by water immersion, acetic acid and AAPH, and has the effect of high gastric mucosal adhesion and improving the defense of gastric mucosa. Polaprezinc can also improve the eradication rate of Helicobacter pylori and has the effect of resisting liver fibrosis, so the drug may have broad clinical application prospects.
[0003] Polaprezinc is an anti-ulcer drug first developed by Hamari New Drug Co., Ltd. of Japan, and is also the first zinc-containing compound used in clinical practice. It was first marketed in Japan under the trade name Promac, and the currently marketed dosage forms are granules and oral disintegrating tablets, which are used for the prevention and treatment of gastric ulcer and inflammatory bowel disease.
[0004] Compared with ordinary oral preparations such as granules, oral disintegrating tablets do not need to be taken with water and can be quickly disintegrated into fine particles in the oral cavity, and the drug taking process can be completed in only a few swallowing actions, so that the oral disintegrating tablets have fast absorption, high bioavailability and convenient taking. Moreover, the preparation is absorbed through the sublingual mucosa and directly enters the blood, effectively avoiding the first-pass effect, so it has the advantages of small dosage, good safety and rapid action, and improves the drug taking compliance of patients including the elderly, children and patients with difficulty in swallowing.
[0005] However, the preparation of oral disintegrating tablets has the following technical bottlenecks: the selection of excipients, the selected excipients should make the prepared tablets have certain hardness and porosity on the basis of ensuring rapid disintegration; the problem of moisture absorption, because oral disintegrating tablets can be completely disintegrated with a small amount of water, they are particularly prone to moisture absorption and fragmentation in a high humidity environment; the problem of taste, this dosage form is released in the oral cavity, so drugs with bitter taste or strong irritating taste should not be prepared into this preparation, especially for drugs with strong bitter taste, only adding aromatic agents or flavoring agents is not enough to improve the taste.
[0006] JP5420321B discloses a polyprene zinc oral disintegrating tablet prepared by kneading, granulating a composition of active ingredient and organic acid such as citric acid, malic acid, tartaric acid, etc., and then adding other excipients. The hardness of the obtained oral disintegrating tablet is unstable, and after only one week of storage at 25℃, 75% RH, the hardness shows a significant change of -2~+30%. The preparation process is also relatively complex, and needs to go through two mixing and granulation processes. The preparation process in this patent and the two granulations therein have a great influence on the hardness and disintegration time of the oral disintegrating tablet, and this technical problem is also explicitly pointed out in the subsequent patent application JP2017002045A.
[0007] JP2017002045A discloses a polyprene zinc oral disintegrating tablet, which is prepared by pre-wet granulation of active ingredient, part of mannitol, disintegrating agent, binder, flavoring agent, and then adding the remaining mannitol and other excipients. The hardness stability of the obtained oral disintegrating tablet is poor, and the D50 of the active ingredient has a great influence on the hardness and storage stability of the oral disintegrating tablet, which needs to be strictly controlled within 15~75μm. Even if the particle size is controlled within the preferred D50 range, the hardness of the obtained tablet is significantly reduced after 1 day of storage, for example, the hardness is reduced by 8~23N after only 1 day of storage at 30℃, 75% RH.
[0008] CN107865827B discloses a polyprene zinc oral disintegrating tablet, which is prepared by mixing polyprene zinc, filler, flavoring agent and part of disintegrating agent uniformly, then adding an appropriate amount of 50% ethanol solution for wet granulation, and then mixing the remaining disintegrating agent with the dry granules uniformly. This patent uses citric acid and sodium bicarbonate to produce a large amount of bubbles in contact with a small amount of water, which can accelerate the disintegration of the tablet. The hygroscopicity of the obtained oral disintegrating tablet still needs to be improved, and the hardness also needs to be improved to avoid fragmentation during transportation or storage.
[0009] Polyprene zinc raw material is insoluble in water and difficult to dissolve in organic solvents, and has hygroscopicity, adhesion and bitterness, which increases the difficulty of prescription design and preparation process when it is made into an oral disintegrating tablet, and also needs to be reasonably designed to improve the taste. The above-mentioned existing oral disintegrating tablets still have defects in dealing with these problems, resulting in many places that need to be improved in the hardness, hygroscopicity, etc. of the obtained product. SUMMARY
[0010] In view of the deficiencies of polyprene zinc preparations in the prior art, the present application provides a polyprene zinc oral disintegrating tablet, which solves the problem of sticking caused by the high hygroscopicity and adhesion of the raw material during tabletting. The obtained oral disintegrating tablet not only disintegrates very quickly, but also has a certain hardness, good taste, content uniformity and stability.
[0011] The inventors discovered in their research that controlling the ambient humidity can alleviate the sticking and punching problem during the tableting process of polyprednisolone zinc orally disintegrating tablets, but it cannot completely solve the sticking and punching problem caused by the high hygroscopicity and adhesion of the active pharmaceutical ingredient. Given the taste requirements of orally disintegrating tablets, it was found that a relatively large amount of flavoring agent needs to be added when preparing orally disintegrating tablets of polyprednisolone zinc, which has a bitter taste.
[0012] To address the above problems, the technical solution of the present invention is as follows:
[0013] A polyprene zinc orally disintegrating tablet comprises polyprene zinc, a surfactant, a filler, a disintegrant, and a lubricant.
[0014] Preferably, in the orally disintegrating tablets, the surfactant has an HLB value of 8 to 12.
[0015] More preferably, in the orally disintegrating tablets, the surfactant is selected from one or more of polyethylene glycol-7-stearate, oleoyl polyoxyethylene glycerol ester, linoleoyl polyoxyethylene glycerol ester, lauroyl polyoxyethylene glycerol ester, or octanoic acid-capric acid-polyethylene glycol glycerol ester.
[0016] Preferably, in the orally disintegrating tablets, the weight ratio of polypyrene zinc to surfactant is 1:0.02 to 0.12, more preferably 1:0.04 to 0.08.
[0017] Preferably, in the orally disintegrating tablets, the filler is selected from one or more of maltodextrin, xylitol, lactose, erythritol or maltitol.
[0018] More preferably, in the orally disintegrating tablets, the filler is selected from maltodextrin, xylitol, or lactose.
[0019] Preferably, in the orally disintegrating tablets, the weight ratio of polypyrrolizumab to the filler is 1:0.3 to 3, more preferably 1:0.8 to 1.2.
[0020] Preferably, in the orally disintegrating tablets, the disintegrant is selected from one or more of sodium carboxymethyl starch, croscarmellose sodium, guar gum, or calcium carboxymethyl cellulose.
[0021] Preferably, in the orally disintegrating tablets, the weight ratio of polypyridazine zinc to disintegrant is 1:0.05 to 0.3, more preferably 1:0.1 to 0.2.
[0022] Preferably, in the oral disintegrating tablet, the lubricant is selected from one or more of calcium stearate, sodium fumarate stearate, magnesium stearate, and micronized silica gel.
[0023] Preferably, the weight ratio of the polyprene zinc to the lubricant is 1:0.001 to 0.005.
[0024] This invention also provides a method for preparing polyprepared zinc orally disintegrating tablets, comprising the following steps: adding polyprepared zinc and a surfactant to a ball mill for co-grinding; after grinding, testing the co-ground material to control the particle size D90≤35um; then adding fillers, disintegrants, and lubricants, and compressing the tablets.
[0025] Preferably, in the preparation method, the grinding beads in the ball mill are 3-10 mm, and more preferably 5 mm.
[0026] More preferably, in the preparation method, the co-grinding time is 0.5 to 1 hour.
[0027] Preferably, in the preparation method, the particle size D90 is controlled to be ≤20 μm.
[0028] Preferably, in the preparation method, the tableting method is either direct powder compression or dry granulation tableting; more preferably, the tableting method is direct powder compression.
[0029] Compared with the prior art, the present invention has the following outstanding advantages:
[0030] 1. This invention solves the sticking problem caused by the high hygroscopicity and adhesion of the active pharmaceutical ingredient during the compression of polypred zinc tablets. This effect is significantly better than the solution of simply relying on controlling the ambient humidity to reduce sticking. The method of pre-co-grinding the active pharmaceutical ingredient and surfactant in this invention makes the formulation operation simple, does not require strict control of the ambient humidity, and can also avoid problems such as tablet surface defects and uneven tablet weight caused by sticking.
[0031] 2. The orally disintegrating tablets obtained by the present invention, by using the method of pre-grinding the raw drug and surfactant, can also mask the bitterness of the raw drug, improve the taste, and help improve patient compliance with medication, thus avoiding the use of a large amount of flavoring agents;
[0032] 3. The orally disintegrating tablets obtained by this invention not only have extremely strong disintegration and dissolution properties, rapidly disintegrating in the oral cavity and uniformly dispersing into small particles, but also have disintegration and dissolution properties that ordinary tablets cannot match. They are absorbed quickly after ingestion and have high bioavailability. They also have a certain degree of hardness to prevent breakage during transportation or storage.
[0033] 4. The preparation process of the orally disintegrating tablets of the present invention is simple, avoiding cumbersome process operations, and the resulting orally disintegrating tablets have high stability. Detailed Implementation
[0034] The following specific embodiments further illustrate the present invention, but do not limit the scope of the present invention in any way. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not depart from the basic idea of the present invention, they are all within the scope of the present invention.
[0035] Example 1
[0036] 1) Prescription
[0037]
[0038] 2) Preparation process
[0039] The prescribed amount of zinc polyprene and the surfactant polyethylene glycol-7-stearate were added to a ball mill with 5mm grinding beads and ground for 0.8 hours. After grinding, the particle size D90 of the co-ground material was tested and found to be ≤20um. The fillers maltodextrin and lactose, the disintegrant sodium carboxymethyl starch, and the lubricant calcium stearate were passed through an 80-mesh sieve and a 100-mesh sieve, respectively. The sieved fillers and disintegrants were then added to the co-ground material and mixed evenly. The sieved lubricant was then added and mixed evenly. The powder was directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75mg of zinc polyprene. After the finished product passed the inspection, it was packaged in double aluminum foil and boxed.
[0040] Example 2
[0041] 1) Prescription
[0042]
[0043]
[0044] 2) Preparation process
[0045] The prescribed amount of polyprene zinc and the surfactant oleoyl polyoxyethylene glycerol were added to a ball mill with 5mm grinding beads and ground for 0.8 hours. After grinding, the particle size D90 of the co-ground material was tested and found to be ≤20um. The filler xylitol and the disintegrant sodium croscarmellose were passed through an 80-mesh sieve, and the lubricant sodium stearate fumarate was passed through a 100-mesh sieve. The sieved filler and disintegrant were then added to the co-ground material and mixed evenly. The sieved lubricant was then added and mixed evenly. The powder was directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75mg of polyprene zinc. After the finished product passed the inspection, it was packaged in double aluminum foil and boxed.
[0046] Example 3
[0047] 1) Prescription
[0048]
[0049] 2) Preparation process
[0050] The prescribed amount of zinc polyprene and the surfactant linoleyl polyoxyethylene glycerol were added to a ball mill with 10mm grinding beads and ground for 0.5 hours. After grinding, the particle size D90 of the co-ground material was tested and found to be ≤35um. The filler erythritol and disintegrant guar gum were passed through an 80-mesh sieve, and the lubricant magnesium stearate was passed through a 100-mesh sieve. The sieved filler and disintegrant were then added to the co-ground material and mixed evenly. The sieved lubricant was then added and mixed evenly. The powder was directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75mg of zinc polyprene. After the finished product passed the inspection, it was packaged in double aluminum foil and boxed.
[0051] Example 4
[0052] 1) Prescription
[0053]
[0054]
[0055] 2) Preparation process
[0056] The prescribed amount of zinc polyprene, along with the surfactants lauroyl polyoxyethylene glycerol ester and caprylic / capric glycerol ester, was added to a ball mill with 5mm grinding beads. The mixture was ground for 1 hour. After grinding, the particle size (D90) of the co-ground material was measured to be ≤20µm. The filler maltitol and disintegrant calcium carboxymethyl cellulose were passed through an 80-mesh sieve, and the lubricant micronized silica gel was passed through a 100-mesh sieve. The sieved filler and disintegrant were then added to the co-ground material and mixed thoroughly. The sieved lubricant was then added and mixed thoroughly. The powder was directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75mg of zinc polyprene. After passing quality inspection, the finished product was packaged in double aluminum foil and boxed.
[0057] Example 5
[0058] 1) Prescription
[0059]
[0060] 2) Preparation process
[0061] The prescribed amount of polyprene zinc and the surfactant oleoyl polyoxyethylene glycerol were added to a ball mill with 5mm grinding beads and ground for 0.8 hours. After grinding, the particle size D90 of the co-ground material was tested and found to be ≤20um. The filler xylitol and the disintegrant sodium croscarmellose were passed through an 80-mesh sieve, and the lubricant sodium stearate fumarate was passed through a 100-mesh sieve. The sieved filler and disintegrant were then added to the co-ground material and mixed evenly. The sieved lubricant was then added and mixed evenly. The powder was directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75mg of polyprene zinc. After the finished product passed the inspection, it was packaged in double aluminum foil and boxed.
[0062] Example 6
[0063] 1) Prescription
[0064]
[0065]
[0066] 2) Preparation process
[0067] The prescribed amount of polyprene zinc and the surfactant oleoyl polyoxyethylene glycerol were added to a ball mill with 5mm grinding beads and ground for 5 minutes. After grinding, the particle size D90 of the co-ground material was tested and found to be ≤100um. The filler xylitol and the disintegrant sodium croscarmellose were passed through an 80-mesh sieve, and the lubricant sodium stearate fumarate was passed through a 100-mesh sieve. The sieved filler and disintegrant were then added to the co-ground material and mixed evenly. The sieved lubricant was then added and mixed evenly. The powder was directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75mg of polyprene zinc. After the finished product passed the inspection, it was packaged in double aluminum foil and boxed.
[0068] Example 7
[0069] 1) Prescription
[0070]
[0071] 2) Preparation process
[0072] The prescribed amount of polyprene zinc and the surfactant glyceryl monostearate were added to a ball mill with 5mm grinding beads and ground for 0.8 hours. After grinding, the particle size D90 of the co-ground material was tested and found to be ≤20um. The filler xylitol and the disintegrant sodium croscarmellose were passed through an 80-mesh sieve, and the lubricant sodium stearate fumarate was passed through a 100-mesh sieve. The sieved filler and disintegrant were then added to the co-ground material and mixed evenly. The sieved lubricant was then added and mixed evenly. The powder was directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75mg of polyprene zinc. After the finished product passed the inspection, it was packaged in double aluminum foil and boxed.
[0073] Example 8
[0074] 1) Prescription
[0075]
[0076]
[0077] 2) Preparation process
[0078] The prescribed amount of Zinc P-Repair and the surfactant Tween 20 were added to a ball mill with 5mm grinding beads and ground for 0.8 hours. After grinding, the particle size D90 of the co-ground material was tested and found to be ≤20um. The filler xylitol and the disintegrant sodium croscarmellose were passed through an 80-mesh sieve, and the lubricant sodium stearate fumarate was passed through a 100-mesh sieve. The sieved filler and disintegrant were then added to the co-ground material and mixed evenly. The sieved lubricant was then added and mixed evenly. The powder was directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75mg of Zinc P-Repair. After the finished product passed the inspection, it was packaged in double aluminum foil and boxed.
[0079] Comparative Example 1
[0080] 1) Prescription
[0081]
[0082] 2) Preparation process
[0083] The prescribed amounts of zinc polyprene, surfactant oleoyl polyoxyethylene glycerol, filler xylitol, and disintegrant sodium croscarmellose are passed through an 80-mesh sieve, while the lubricant sodium stearate fumarate is passed through a 100-mesh sieve. The sieved zinc polyprene, surfactant, filler, and disintegrant are then mixed evenly. The sieved lubricant is then added and mixed evenly. The powder is directly compressed into tablets at a pressure of 6.5–9.0 kN, with each tablet containing 75 mg of zinc polyprene. After the finished product passes inspection, it is packaged in double aluminum foil and boxed.
[0084] Comparative Example 2
[0085] 1) Prescription
[0086]
[0087]
[0088] 2) Preparation process
[0089] The prescribed amount of zinc peptide, xylitol as filler, and sodium croscarmellose as disintegrant are passed through an 80-mesh sieve, and sodium stearate fumarate as lubricant is passed through a 100-mesh sieve. Then, the sieved zinc peptide, filler, and disintegrant are mixed evenly. The sieved lubricant is then added and mixed evenly. The powder is directly compressed into tablets at a pressure of 6.5–9.0 KN. Each tablet contains 75 mg of zinc peptide. After the finished product passes the inspection, it is packaged in double aluminum foil and boxed.
[0090] Comparative Example 3
[0091] 1) Prescription
[0092]
[0093] 2) Preparation process
[0094] Weigh out the prescribed amounts of zinc polymethyl methacrylate, erythritol, sodium saccharin, citric acid, and a portion of microcrystalline cellulose. Mix them thoroughly in a mixer, add 50% ethanol solution as a wetting agent, stir for 5 minutes, granulate using a 40-mesh sieve, and dry in a ventilated environment at 50℃±5℃. Sieve the dried granules through a 40-mesh sieve to granulate, record the weight of the dried granules, and use this to calculate the dosage of the added excipients: microcrystalline cellulose, low-substituted hydroxypropyl cellulose, sodium bicarbonate, talc, magnesium stearate, and menthol. Weigh out the calculated amounts of the added excipients and mix them thoroughly with the dried granules. Take samples for testing, compress the qualified tablets, and after the finished product passes inspection, package them in double aluminum foil and box them.
[0095] Comparative Example 4
[0096] The following ingredients were mixed and granulated: 67.6% Zinc P-P-Resin, 14.7% D-mannitol, 0.9% hydroxypropyl cellulose, 10.8% cropovidone, 5.9% crystalline cellulose, and sucralose. The granules were then dried in a dryer. 85.3% of the granules were mixed with 12.7% D-mannitol, 0.8% low-substituted hydroxypropyl cellulose, trace amounts of L-menthol, trace amounts of flavoring, and 1.0% magnesium stearate. The mixture was then compressed into tablets containing approximately 75 mg of Zinc P-P-Resin per 130 mg tablets using a rotary tablet press. After passing the finished product inspection, the tablets were packaged in double aluminum foil and boxed.
[0097] Verification Implementation Examples
[0098] Experimental Example 1: Determination of the appearance, taste, and dissolution of the obtained formulation
[0099] The method for testing the texture: Ten teenagers aged 18 to 22 were evaluated. The evaluators should be able to correctly taste the different fineness and hardness of the oral disintegrating tablets. The effect of the oral disintegrating tablets was determined by the smoothness of the surface, the delicate taste without gritty feeling, the moderate softness and hardness, and the good taste.
[0100] Dissolution test: The active ingredient of this invention has poor solubility; therefore, according to the pharmacopoeia, its dissolution characteristics need to be examined. Tablets obtained from each example and comparative example (6 tablets of each) were tested using the test apparatus of Method 2, Dissolution Test Method 0931, Part IV of the 2020 edition of the Chinese Pharmacopoeia. 500 mL of phosphate buffer solution at pH 6.8 was used as the dissolution medium, and the rotation speed was 50 rpm. Samples were taken at 5, 10, and 15 minutes to detect the dissolution amount. The results are shown in Table 1.
[0101] Table 1. Measurement results of Examples 1-8 and Comparative Examples 1-4
[0102]
[0103] The results showed that the orally disintegrating tablets obtained in Examples 1-6 had better appearance, taste, and dissolution. In Examples 7 and 8, glyceryl monostearate and Tween 20 were used as surfactants, respectively. The resulting orally disintegrating tablets were sticky, resulting in a spotted appearance, a slightly bitter taste, a gritty texture, and a slower dissolution rate. In contrast, Example 1 did not pre-grind the active pharmaceutical ingredient and surfactant, nor did it add any flavoring agent. The resulting formulation had more spots, a bitter taste, a noticeable gritty texture, and slower dissolution. In contrast, Example 2 did not use any surfactant or flavoring agent, and the resulting formulation had poorer properties and dissolution. In contrast, the orally disintegrating tablets obtained in Examples 3 and 4 dissolved more slowly.
[0104] Experimental Example 2: Investigation of the content uniformity, hardness, disintegration time and stability of the obtained formulation
[0105] Content uniformity determination: The content uniformity test was performed according to the content uniformity test method in General Chapter 0941 of Part IV of the Chinese Pharmacopoeia. The standard is A+2.2S≤15.
[0106] Hardness determination: Ideally, orally disintegrating tablets should have both a suitable lower and upper hardness limit. The lower hardness limit should provide sufficient compressive strength for smooth production, packaging, and transportation. Generally, the hardness requirements for ordinary tablets in Part IV of the Chinese Pharmacopoeia can be referenced, namely a hardness above 50 N and a tensile strength of 1.5–3.0 MPa. The determination method is as follows: using a tablet hardness tester, under specified conditions, 10 tablets are tested consecutively at once, and the average hardness and the hardness value of each tablet are recorded.
[0107] Disintegration time determination: Referencing the disintegration time test method for orally disintegrating tablets in General Chapter 0921 of the 2020 edition of the Chinese Pharmacopoeia, Part IV, the instrument consists of a liftable support and a stainless steel tube with a sieve at the lower end. The liftable support moves up and down at a frequency of 30 times per minute. The disintegration basket is a 30mm long stainless steel tube with an inner diameter of 13.0mm, and the stainless steel sieve (embedded at the bottom of the tube) has an inner diameter of 710µm. In the test method, the stainless steel tube is fixed to the support and immersed in a 1000mL cup containing approximately 900mL of water at 37℃ ± 1℃. The water level is adjusted so that the sieve is 15mm ± 1mm below the water surface when the stainless steel tube is at its lowest position. The instrument is then started. Take one tablet of this product and place it in the aforementioned stainless steel tube for testing. It should completely disintegrate and pass through the sieve within 60 seconds. If a small amount of light matter floats to the top or adheres to the inner wall of the stainless steel tube or the sieve, but has no hard core, it can be considered compliant. Repeat the test on 6 tablets; all should comply with the requirements. If one tablet fails to comply, take another 6 tablets for retesting; all should comply with the requirements.
[0108] Accelerated stability test: The sample was placed at a temperature of 40±2℃ and a relative humidity of 75±5% (accelerated) for 6 months. Samples were taken at the end of the 0th, 3rd and 6th months, and the related substances (total impurities, %) were determined.
[0109] Table 2 shows the measurement results of Examples 1-8 and Comparative Examples 1-4.
[0110]
[0111]
[0112] The results showed that the orally disintegrating tablets obtained in Examples 1-6 had high content uniformity and hardness, short disintegration time, and low content of related substances. Examples 7 and 8 used glyceryl monostearate and Tween 20 as surfactants, respectively, which slightly reduced the content uniformity and hardness of the orally disintegrating tablets and increased the content of related substances. Compared with Example 1, which did not pre-grind the active pharmaceutical ingredient and surfactant, the resulting formulation had poor content uniformity and hardness, and increased content of related substances. Compared with Example 2, which did not use surfactant, the resulting formulation also had poor content uniformity and hardness, and increased content of related substances. Compared with Examples 3 and 4, the orally disintegrating tablets had poor content uniformity and hardness, possibly due to the wet granulation process used, which resulted in higher content of related substances in the orally disintegrating tablets.
Claims
1. A poly- zinc oxide orally disintegrating tablet, characterized in that, The oral disintegrating tablet comprises polaprezinc, a surfactant, a filler, a disintegrating agent and a lubricant.
2. The orally disintegrating tablet according to claim 1, wherein In the oral disintegrating tablet, the HLB value of the surfactant is 8-12.
3. The orally disintegrating tablet according to claim 2, wherein In the oral disintegrating tablet, the surfactant is selected from one or more of polyethylene glycol-7-stearate, oleoyl polyoxylethylene glycerides, linoleoyl polyoxylethylene glycerides, lauroyl polyoxylethylene glycerides or caprylocaproyl polyoxylethylene glycerides.
4. The orally disintegrating tablet according to claim 1, wherein In the oral disintegrating tablet, the weight ratio of polaprezinc to the surfactant is 1:0.02-0.
12.
5. The orally disintegrating tablet according to claim 1, wherein In the oral disintegrating tablet, the filler is selected from one or more of maltodextrin, xylitol, lactose, erythritol or maltitol.
6. The orally disintegrating tablet according to claim 1, wherein In the oral disintegrating tablet, the weight ratio of polaprezinc to the filler is 1:0.3-3.
7. The orally disintegrating tablet according to claim 1, wherein In the oral disintegrating tablet, the disintegrating agent is selected from one or more of sodium carboxymethyl starch, sodium crosscarmellose, guar gum or calcium carboxymethyl cellulose.
8. The orally disintegrating tablet according to claim 1, wherein In the oral disintegrating tablet, the weight ratio of polaprezinc to the disintegrating agent is 1:0.05-0.
3.
9. A process for the preparation of the orally disintegrating tablet according to claim 1, characterized in that, The preparation method comprises the following steps: polaprezinc and a surfactant are added into a ball mill for co-milling, after the milling is completed, the co-milled substance is detected for qualification, and then a filler, a disintegrating agent and a lubricant are added for tabletting.
10. The production method according to claim 9, wherein In the preparation method, the qualification standard for the co-milled substance is to control the particle size D90≤35 um.
Citation Information
Patent Citations
A pharmaceutical composition for orally disintegrating polyprednisolone tablets and its preparation method
CN107865827B
Operational order selector
JP1979020321A
Orally disintegrating tablet
JP2017002045A